(537) Decision model for one year planning نموذج القرار للتخطيط لمدة سنة واحدة - Hamid, Salah; Amer, Roshdi (The Institute of National Planning, 2025)
The study addresses the problem of optimizing the allocation of foreign resources (imports) across various economic sectors for a given year. The solution must satisfy several conditions: restrictions on sectoral production changes, fixed production levels for agriculture and ginning, no competitive imports in the ginning sector, and upper and lower bounds on private and government consumption, investments, exports, and total labor. Additionally, the value-added from service sectors cannot exceed a specified ratio of the total value-added across all sectors. The goal is to maximize labor and national income, weighted differently, using interflow analysis and linear programming techniques. This approach ensures efficient and balanced resource distribution within the economy